Lab-on-a-chip : techniques, circuits, and biomedical applications - Ghallab, Yehya H.; Badawy, Wael (Artech House integrated microsystems series., 2010)
"Here's a groundbreaking book that introduces and discusses the important aspects of lab-on-a-chip, including the practical techniques, circuits, microsystems, and key applications in the biomedical, biology, and life science fields. Moreover, this volume covers ongoing research in lab-on-a-chip integration and electric field imaging. Presented in a clear and logical manner, the book provides you with the fundamental underpinnings of lab-on-a-chip, presents practical results, and brings you up to date with state-of-the-art research in the field. This unique resource is supported with over 160 illustrations that clarify important topics throughout."--Publisher's description.